menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Convert the equation to the standard form for a hyperbola by completing the square on x and y. x2 - y2 + 6x - 4y + 4 = 0? (x + 3)2 + (y + 2)2 = 1 (x + 3)2 - (y + 2)2 = 1 (y + 3)2- (x + 2)2 = 1 (y+3)^2/16
asked
Jan 3, 2019
226k
views
0
votes
Convert the equation to the standard form for a hyperbola by completing the square on x and y. x2 - y2 + 6x - 4y + 4 = 0?
(x + 3)2 + (y + 2)2 = 1
(x + 3)2 - (y + 2)2 = 1
(y + 3)2- (x + 2)2 = 1
(y+3)^2/16 − (x+2)^2/36 = 1
Mathematics
high-school
Janna Maas
asked
by
Janna Maas
5.4k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
3
votes
x² + 6x + ____ - (y² + 4y + ____ ) = -4 + ____ + ____
x² + 6x + 9 - (y² + 4y + 4 ) = -4 + 9 + -4
(x + 3)² - (y + 2)² = 1
Answer: B
Leonso Medina Lopez
answered
Jan 8, 2019
by
Leonso Medina Lopez
5.2k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.8m
questions
7.5m
answers
Other Questions
Aliyah has $24 to spend on seven pencils. After buying them she had $10. How much did each pencil cost?
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Find the quotient of 3,078 ÷ 27. A) 104 B) 109 C) 114 D) 119
Can someone help me with 5??? ASAP?
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org